Eye health and quality of life: an umbrella review protocol. Issue 8 (30th August 2020) - Assi, Lama; Rosman, Lori; Chamseddine, Fatimah; Ibrahim, Perla; Sabbagh, Hadi; Congdon, Nathan; Evans, Jennifer; Ramke, Jacqueline; Kuper, Hannah; Burton, Matthew J; Ehrlich, Joshua R; Swenor, Bonnielin K
Abstract : Introduction: Vision impairment and eye disease are major global health concerns and have been associated with increased morbidity and mortality, and lower quality of life. Quality of life, whether generic, vision-specific or disease-specific, is an important measure of the impact of eye health on people's daily activities, well-being and visual function, and is increasingly used to evaluate the impact of ophthalmic interventions and new devices. While many studies and reviews have examined the relationship between vision or eye health and quality of life across different contexts, there has yet to be a synthesis of the impact of vision impairment, eye disease and ophthalmic interventions on quality of life globally and across the lifespan. Methods and analysis: An umbrella review of systematic reviews will be conducted to address these two questions: (1) What is the association of vision impairment and eye disease with quality of life? (2) What is the impact of ophthalmic interventions on quality of life? A search of related literature will be performed on the 11 February 2020 in Medline Ovid, Embase.com, Cochrane Database of Systematic Reviews, Proquest Dissertations and Theses Global, and the grey literature, and repeated at the synthesis stage. Title/abstract and full-text screening, methodological quality assessment and data extraction will be conducted by reviewers working independently and in duplicate. Assessment of methodological quality and data extraction will be performed using Joanna Briggs Institute standard forms. Findings from the systematic reviews and their methodological quality will be summarised qualitatively in the text and using tables. Ethics and dissemination: No ethical approval is required. Results of this umbrella review will be published in a peer-reviewed journal and summarised in the Lancet Global Health Commission on Global Eye Health. Trial registration number: This protocol was registered in the Open Science Framework Registries (https://osf.io/qhv9g/ ).